Comparing acquired angioedema with hereditary angioedema (types I/II): findings from the Icatibant Outcome Survey. (9th February 2017) - Longhurst, H. J.; Zanichelli, A.; Caballero, T.; Bouillet, L.; Aberer, W.; Maurer, M.; Fain, O.; Fabien, V.; Andresen, I.; ,
Summary: Icatibant is used to treat acute hereditary angioedema with C1 inhibitor deficiency types I/II (C1‐INH‐HAE types I/II) and has shown promise in angioedema due to acquired C1 inhibitor deficiency (C1‐INH‐AAE). Data from the Icatibant Outcome Survey (IOS) were analysed to evaluate the effectiveness of icatibant in the treatment of patients with C1‐INH‐AAE and compare disease characteristics with those with C1‐INH‐HAE types I/II. Key medical history (including prior occurrence of attacks) was recorded upon IOS enrolment. Thereafter, data were recorded retrospectively at approximately 6‐month intervals during patient follow‐up visits. In the icatibant‐treated population, 16 patients with C1‐INH‐AAE had 287 attacks and 415 patients with C1‐INH‐HAE types I/II had 2245 attacks. Patients with C1‐INH‐AAE versus C1‐INH‐HAE types I/II were more often male (69 versus 42%; P = 0·035) and had a significantly later mean (95% confidence interval) age of symptom onset [57·9 (51·33–64·53) versus 14·0 (12·70–15·26) years]. Time from symptom onset to diagnosis was significantly shorter in patients with C1‐INH‐AAE versus C1‐INH‐HAE types I/II (mean 12·3 months versus 118·1 months; P = 0·006). Patients with C1‐INH‐AAE showed a trend for higher occurrence of attacks involving the face (35 versus 21% of attacks; P = 0·064). Overall, angioedema attacks were more severe in patients with C1‐INH‐HAE types I/II versus C1‐INH‐AAE (61 versus 40% of attacks were classified as severe to very severe; P < 0·001). Median total attack duration was 5·0 h and 9·0 h for patients with C1‐INH‐AAE versus C1‐INH‐HAE types I/II, respectively. Abstract : Real‐world data from the Icatibant Outcome Survey was used to evaluate the effectiveness of icatibant in the treatment of 16 patients with C1‐INH‐AAE (experiencing 287 attacks) and 415 patients with C1‐INH‐HAE types I/II (experiencing 2245 attacks), and to compare disease characteristics. Time from symptom onset to diagnosis was significantly shorter in patients with C1‐INH‐AAE versus C1‐INH‐HAE types I/II. Angioedema attacks were significantly less severe, and median total attack duration was significantly shorter in patients with C1‐INH‐AAE vs patients with C1‐INH‐HAE types I/II.